Genetic and phenotypic correlation, of reproductive and productive traits in exotic and their crosses with Gaddi sheep in Himachal Pradesh - SINGH, UMESH; MANUJA, N K (The Indian Journal of Animal Sciences, 2013)
In this investigation 501 lambs consisting of 285 Rambouillet, 17 Gaddi, 124 (75%) Rambouillet x (25%) Gaddi, and 55 (75%) Merino x (25%) Gaddi animals were used. The genetic and phenotypic correlations were estimated from sire component of variance and covariance. The traits considered were birth weight, dam’s weight at lambing, lambing intervals, age at first lambing and annual clim yield (1,2 and 3). The genetic and phenotypic correlation of birth weight with dam’s weight at lambing and annual clip yields (1,2 and 3) were highly significant. The genetic and phenotypic correlations among reproductive traits were nonsignificant, Whereas genetic and phenotypic correlation among productive traits were highly significant. A high heritability was also estimated for birth weight, age at first lambing dam’s weight at lambing and annual clip yield (1,2 and 3). Heritability estimates of lambing intervals were low to medium.